(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The purpose of the study was to investigate the electrical activity of selected muscles during spike using electromyography on Inter-University players of volleyball. In volleyball, spike is the most exciting technique which every player likes. In this study fifteen male subjects ranged from Eighteen to Twenty Four years were selected as the subjects from Lakshmibai National University of Physical Education, Gwalior. These all players had represented Inter-University level and they had no upper extremity injuries or any bone or joint disparities within the past years. By reviewing the literature and consultation with experts, the research scholar carried out an intensive study and selected variables were Anterior Deltoid, Medial Deltoid, Biceps Brachii and Triceps Brachii. The criterion measure adopted for this study was measured by Bio Tech Thought Technology of Eight channel. After a brief warm-up, and electrodes placement accoding to SENIAM guidelines and then participants allowed to perform the spike. Three times data were recorded and the best was considered for data. Descriptive statistical and percentile technique were used to find out the muscles, which were more significant during Contact Phase in volleyball. The level of significance was set at 0.05. The findings of the study clearly revealed that electrical activity of Anterior shoulder muscle showed highest activation level of EMG during Contact phase in selected muscle groups. Anterior shoulder muscle and triceps showed high activation which helps to hit the ball more powerfully as they were considered to be prime movers in the hitting phase of spike. Due to coupling force at shoulder joint the contact with the ball is very important, otherwise shoulder injury may take place due to excessive stress on shoulder joint. Whereas other selected muscle like medial deltoid and biceps brachii showed less electrical activation in respect to their maximum voluntary contraction. Hence, spiker should contacts the ball at particular position means in front of the shoulder muscle to increase efficiency and effectiveness of spiking and also include strength training of contributory muscles